Analysis of Health Financing Legal Regulations in the Digital Era: Reviewed from Challenges and Opportunities - Chairul, Muhamamad; Risdawati, Irsyam (CV Raskha Media Group, 2025)
Health financing is an essential aspect of the global health system that affects the accessibility, sustainability, and efficiency of health services. The background of health financing is becoming an increasingly relevant topic in the context of a rapidly evolving global health system, especially with the advancement of digital technology. The digital era offers a variety of innovations that can improve the efficiency and accessibility of health financing, but also pose new challenges for legal regulation. Existing regulations have not fully accommodated the development of digital technology, thus affecting the effectiveness and integrity of the health financing system. This research aims to analyze the legal regulations governing health financing in the digital era and to explore the challenges and opportunities arising from digitalization. The method used in this study is a normative juridical approach, with an analysis of related laws and regulations and comparative study with policies in other countries. The results show that while digital technology offers an excellent opportunity to improve efficiency in health financing, there are various challenges, including misalignment between existing regulations and technological advancements, issues related to personal data protection, and oversight of digital payment systems. However, digitalization also offers an excellent opportunity to create rules that are more flexible and responsive to change, thereby maximizing the potential of technology in the health sector. In conclusion, this study recommends regulatory reforms that are more adaptive to digital developments to create a more efficient, secure, and inclusive health financing system.